Indian Stocks Outflows from FIIS: An Empirical Study in Current Scenario: The Impact of Foreign Institutional Investors on the Indian Stock Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The rising contribution of FIIs (Foreign Institutional Investors) in Indian stock market has risen by many Indians. Their power on stock markets has been extensively debated and remains a hot topic in the media. Being a embryonic country, India attract a large sum of FII every year. Indian Stock Market, which is one of the signs of the financial status, is also being pretentious by the foreign funds made.